Nanotechnology and its Application in Dentistry (2014)
Nanotechnology influences almost every facet of everyday life from security to medicine. The concept of nanotechnology is that when one goes down to the bottom of things, one can discover unlimited possibilities and potential of the basic particle. In nanotechnology, analysis can be made to the level of manipulating atoms, molecules and chemical bonds between them. The growing interest in the dental applications of nanotechnology is leading to the emergence of a new field called nanodentistry. An electronic database search that included PubMed, MedLine, and Cochrane library was conducted. Key words used in the search are nanotechnology dentistry and applications. Language limitation was set as articles reviewed were only those written and published in English language. We did not search the gray literature. Initially, 52 articles were retrieved from the database, and articles considered were those published from 2008 to 2013. Eight articles that met the selection criteria were eventually selected and reviewed.